Antecedents, focus, and outcomes of work-life balance: A conceptual review - Uddin, Mahi (IIUC Business Review, 2022)
Grounded on a thorough literature review, this study proposes a conception about work-life balance (WLB) in an integrated approach, which includes antecedents, focus and outcomes of work-life interface. This framework includes two essential aspects such as, commitment to work and non-work roles and minimum role conflicts between role domains of work and non-work. Based on our conceptualization, this study reviews evidence regarding the consequences of WLB relating to work, personal life and stress outcomes. The study finally reviewed 57 published articles in their entirety out of 181 articles selected through searching databases. The study then pinpoints organizational and personal predictors to WLB and describes their influences on WLB. After that, I explained relevant theoretical approaches are aligning WLB and life satisfaction. The findings explored two key predictors such as organizational and individual, and three key consequences including, work-related, non-work-related, and stress-related consequences. The study further explained several theories relating to WLB and life satisfaction. Finally, I highlight policy implications and directions for future research. IIUC Business Review Vol. 9, Dec. 2020 pp. 27-46